2001
DOI: 10.1083/jcb.152.4.765
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 14-Kilodalton Protein Interacts with the Mitogen-Activated Protein Kinase Scaffold Mp1 on a Late Endosomal/Lysosomal Compartment

Abstract: We have identified a novel, highly conserved protein of 14 kD copurifying with late endosomes/lysosomes on density gradients. The protein, now termed p14, is peripherally associated with the cytoplasmic face of late endosomes/lysosomes in a variety of different cell types.In a two-hybrid screen with p14 as a bait, we identified the mitogen-activated protein kinase (MAPK) scaffolding protein MAPK/extracellular signal–regulated kinase (ERK) kinase (MEK) partner 1 (MP1) as an interacting protein. We confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 52 publications
5
170
1
Order By: Relevance
“…This effect may be due to less efficient pore formation (Fig. 1b) or LF unfolding (25) under more neutral pH conditions; or instead might be due to a reduction in the accessibility of MEK1, which might be concentrated on scaffolds on late endosomes (34), under these conditions. Our results are consistent with different receptor-specific pH requirements for pore formation in the endosomal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to less efficient pore formation (Fig. 1b) or LF unfolding (25) under more neutral pH conditions; or instead might be due to a reduction in the accessibility of MEK1, which might be concentrated on scaffolds on late endosomes (34), under these conditions. Our results are consistent with different receptor-specific pH requirements for pore formation in the endosomal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These include the effectors Rain1 on the Golgi and the activated Raf-MEK-ERK cascade on endosomes [83,84]. Further examples include scaffolds for the Raf-MAPK cascade; whilst KSR is recruited to the cell surface, Sef is localised on the Golgi and p14-MP1 on endosomes [85][86][87][88].…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 99%
“…Our recent observations have suggested a potential role for the MP1-p14 complex in coupling MAP kinase signaling to Rho [126]. MP1 is a small protein (14 kDa) identified as a MEK1 and ERK1 binding partner [127]; p14 is a protein tightly associated with late endodomes and lysosomes that was subsequently found to interact with high affinity with MP1 [128][129][130]. Specifically, we have found that MP1-p14 is important for PAK phosphorylation of MEK1 and ERK activation during adhesion to fibronectin, and that siRNA-mediated depletion of the complex causes a spreading defect in fibroblasts in concert with the formation of dense circumferential F-actin and large vinculin containing adhesions [126].…”
Section: Erk Regulation Of Rho-rock Functionmentioning
confidence: 99%
“…For instance, MP1 associates tightly with p14, a protein tightly associated with late endosomes and lysosomes [129,130], and this localization is important for ERK activation in response to EGF [128]. MP1-p14 appears important for focal adhesion remodeling during cell spreading on fibronectin [126].…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%